(untitled) (Orfeu, 2022)
This article is restricted to the field of artistic research and focuses on the relationship between analysis and musical performance of Lowell Liebermann’s Sonata for flute and piano Op. 23. Establishes a dialogue with the composer through references to a recent interview. Through resources in musical analysis and the authors’ experience in musical performance, it presents compositional aspects of the work, interpretation suggestions and performance strategies.